Instrument for the evaluation of the chronic wounded patient: clinical, care and financial indicators - Taysa de Fátima Garcia; Eline Lima Borges; Claudiomiro da Silva Alonso; Mery Natali Silva Abreu (Universidade Federal do Ceará, 2022)
Objectives: to validate an instrument for the assessment of patients with chronic wounds, and to propose clinical, care and financial indicators for Primary and Secondary Health Care. Methods: methodological study involving the development and validation of an instrument consisting of four dimensions with 90 items. The sample was composed of 21 judges, nurses working in Primary or Secondary Care, who evaluated the dimensions of each item regarding comprehensiveness, clarity, relevance and representativeness. Data were analyzed by descriptive statistics and validation by the Content Validity Index. Results: the mean experience of the judges in Primary Care was 7.4 years and in Secondary Care 7.8 years. The index of content validity of each item of the instrument ranged from 0.95 to one, and of each dimension from 0.99 to one, resulting in an overall value of 0.99. Conclusion: this study enabled the development and validation of the instrument. Contributions to practice: the instrument can parameterize data collection and support the generation of clinical, care and financial indicators of the service.